The Effect of Social Support and Extraversion Personality on Entrepreneurial Interest in Students - Ernawati Ernawati; Ella Anastasya Sinambela; Cici Cici; Resva June Silviana; Roudhotul Nur Azizah; Sohibatun Naudalia (metromedia.education, 2022)
Students are a group in society that obtains its status because of its ties to a university. Higher education certainly produces students who are excellent and competent in their fields. And interest in entrepreneurship. Developed countries both from the economic and industrial sectors are indicated by the entrepreneurial growth index. This study aims to determine the effect of social support and extraversion personality on entrepreneurial interest. The research to be conducted is a quantitative research type. This type of research design uses an Explanatory Survey. This survey was conducted by taking samples from the total population and using a questionnaire as a data collection tool. Furthermore, the methods used are descriptive and verification methods. The sample used in this study amounted to 100 respondents. The analysis carried out in this study used linear regression analysis. The results of this study indicate that social support and extraversion have an effect on interest in entrepreneurship.